Factors influencing exclusive breastfeeding practice in Sleman, Yogyakarta - Alfun Dhiya An; Alfaina Wahyuni; Fitnaningsih Endang Cahyawati; Nurul Izzah Azzahari; Shobiqo Ramdani Putri; Maharani Dyahayu Prameswari; Shoofwah Salsabila Rosas (AcTion: Aceh Nutrition Journal, 2024)
The determinant of children’s nutritional problems in Indonesia is exclusive breastfeeding practice. Sleman Regency has a prevalence of stunting that is higher than the target to achieve in 2024, and the number of exclusive breastfeeding coverage is still low. This study aimed to analyze the factors influencing the success of exclusive breastfeeding in Sleman Yogyakarta. Method, analytical cross-sectional research was conducted under the area of Gamping I Community Health Center, Sleman Regency, in June 2023. The participants were selected using a purposive sampling technique. Chi-square analysis was performed to determine the association and odds ratios between the two variables. Results, from the 100 participants who met the inclusion criteria, this study found that three factors that influenced exclusive breastfeeding practice were the history of Initiation of Early Breastfeeding (IEB) (p = 0,001), mothers’ knowledge level (p = 0,000), and mothers’ lactation management skills (p = 0,000). Mothers who previously had IEB, good knowledge, and good lactation management were more likely to exclusively breastfeed, respectively. Conclusions, IEB improves mothers’ confidence and fosters positive perceptions of breastfeeding. Having good knowledge and good lactating management enhances mothers’ ability to handle breastfeeding challenges and prevent breastfeeding dropout before the baby reaches six months of age.